Pengaruh transisi konsumsi energi fosil menuju energi baru terbarukan terhadap produk domestik bruto di Indonesia - Dikta Muhammad Ferro Berlianto; Riko Setya Wijaya (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2022)
This study aims to determine the impact of the energy transition including consumption of new renewable energy, consumption of fossil energy and production of new and renewable energy on gross domestic product in Indonesia. The data in this research study is secondary data with a period of 20 years, between 2000 and 2019 which was obtained from the International Energy Agency (IEA), International Renewable Energy Agency (IRENA), Asian Development Bank (ADB), and several scientific journals. The analytical method used is multiple linear regression with the assumption of BLUE (Best Linear Unbiased Estimate). The results obtained that the consumption of new and renewable energy has a positive relationship but does not have a significant effect on gross domestic product in Indonesia, while the consumption of fossil energy and also the production of new and renewable energy has a positive relationship and has a significant effect on gross domestic product in Indonesia.